The Impact of Political Efficacy on Citizens’ E-Participation in Digital Government - Ruqiang Lai; Loo-See Beh (Administrative Sciences)
Citizens’ e-participation determines the successes and failures of digital government or e-government. However, its results to date have not been satisfactory. IT adoption models dominate previous studies. However, citizens’ psychological factors have been overlooked. The field has fallen into the trap of “technological solutionism.” This research focuses on political efficacy and collected self-reported data from 388 respondents through an online questionnaire. Partial Least Squares Structural Equation Modeling was carried out for data analyses. The results showed that e-participation intention positively affects e-participation behavior. Both internal political efficacy and external political efficacy have a positive significant relationship with e-participation intention. Additionally, descriptive analysis results revealed the relationships between citizens’ demographic factors and their influence on e-participation, including gender, age, monthly income, education level, political affiliation, and occupation. This research provides further empirical evidence and insightful knowledge for scholars, enriching political efficacy theory. Government officials can benefit from this research where targeted measures can be developed.